MOLECULAR IDENTIFICATION OF MICROSPORUM SPP. THAT CAUSES RINGWORM IN HUMAN AND SOME ANIMALS - Laila Jasim Shaebth; Louhichi Nacim (Journal for Technology and Science, 2026)
Objective: To molecularly identify and determine the prevalence of Microsporum species from clinical isolates of both human and animal populations. Method: A total of 427 isolates, comprising 248 from human populations and 179 from animal populations, were included in the study. The molecular identification of Microsporum species from the isolates was performed by conventional PCR using the Internal Transcribed Spacer (ITS) regions, followed by PCR-RFLP using the MvaI restriction enzyme. Results: In the present study, Microsporum canis was found to be the predominant species, responsible for causing dermatophytosis in both human populations, where it accounted for 58.9% (146/248) of the isolates, and animal populations, where it accounted for 82.1% (147/179) of the isolates. In the human population, the second most common species, after M. canis, were M. audouinii (22.2%), M. gypseum (12.5%), and M. ferrugineum (5.2%). In the animal populations, M. gypseum was found to account for 14.5%, with small percentages of M. nanum (2.2%). Novelty: The effectiveness of the PCR-RFLP method for species differentiation is evident from the results, where each species of Microsporum produced unique banding patterns. For instance, M. canis produced bands at 329bp, M. gypseum produced bands at 186bp, while M. audouinii produced bands at 125bp.